2021
DOI: 10.3390/nu13082544
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Mediated Activation of Neuronal Cells Triggered by γ-Aminobutyric Acid (GABA)

Abstract: γ-Aminobutyric acid (GABA) is a potent bioactive amino acid, and several studies have shown that oral administration of GABA induces relaxation, improves sleep, and reduces psychological stress and fatigue. In a recent study, we reported that exosomes derived from GABA-treated intestinal cells serve as signal transducers that mediate brain–gut interactions. Therefore, the purpose of this study was to verify the functionality of GABA-derived exosomes and to examine the possibility of improving memory function f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…After washing the cells, the cells were treated with a blocking buffer (1 × PBS, 5% goat serum, and 0.3% Triton X-100) for 1 h, and subsequently with Milli-Mark Pan Neuronal Marker (Merck Millipore, Billerica, MA, USA) at 25 °C overnight. After washing the cells, the cells were stained with Alexa Fluor 555 goat anti-rabbit IgG antibody (Thermo Fisher Scientific, Inc., Tokyo, Japan) and Hoechst 33342, and neurite outgrowth was quantitatively determined using the IN Cell Analyzer 2200 (Cytiva, Tokyo, Japan), as previously described [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After washing the cells, the cells were treated with a blocking buffer (1 × PBS, 5% goat serum, and 0.3% Triton X-100) for 1 h, and subsequently with Milli-Mark Pan Neuronal Marker (Merck Millipore, Billerica, MA, USA) at 25 °C overnight. After washing the cells, the cells were stained with Alexa Fluor 555 goat anti-rabbit IgG antibody (Thermo Fisher Scientific, Inc., Tokyo, Japan) and Hoechst 33342, and neurite outgrowth was quantitatively determined using the IN Cell Analyzer 2200 (Cytiva, Tokyo, Japan), as previously described [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…MagCapture Exosome Isolation PS Kit Ver. 2 (FUJIFILM Wako Pure Chemical Corp.) was used to isolate exosomes from the media of C2C12 cells as described previously [ 8 ]. The amount of exosome used for each experiment was prepared as protein equivalent as measured by MicroBCA Protein Assay Kit (Thermo Fisher Scientific Inc.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that, whether exosomes mediate GABAceptive and GABAergic astrocyte-dependent regulation of neuronal cells has emerged as an interesting question. It has been reported that exosomes derived from GABA-treated intestinal cells or from the serum of GABA-treated mice are able to activate neuronal cells in vitro by affecting the expression of genes related to memory in the hippocampus (Inotsuka et al, 2021). Besides, although in the absence of direct causal evidence, hyperactivation of GABA receptors and the abnormal release of exosomes have been closely linked to neurological disorders including epilepsy (Khalyfa and Sanz-Rubio, 2019).…”
Section: Are Exosomes Able To Mediate Gabaceptive and Gabaergic Astro...mentioning
confidence: 99%
“…Katakura et al treated human gut epithelial Caco-2 cells with γaminobutyric acid (GABA) and found that GABA-induced gut exosomes facilitated neurite growth in SH-SY5Y cells [66]. They also confirmed that exosomes from the serum of oral-GABA-administered mice promoted neurite growth [67]. The direct effect of dietary GABA on sleep and stress in humans is still controversial because it has long been considered that GABA cannot cross the human BBB [68,69].…”
Section: Gut-released Evsmentioning
confidence: 99%